The role of media language in creating coexistence in conflict society (Raparin Journal of Humanities (RJH), 2020)
Language in most societies is a key role in creating coexistence, peace, social and security. However, this can only happen when the language is taken as an important part of the constitution and the law of that country, which have to be constituted as a way of beginning for coexistence. Furthermore, at the same time the education system and the media have also to be put to serve and create a suitable language for coexistence. The opposite is also true, where language is an identity; it is a way of dialogue, word or a term that are used. It is misunderstanding between some people in some societies that language has become a source for the mayhem, conflicts, economic crisis and the disruption of national and social security especially in those countries and societies that are passing through the transition stages. Which is also multinational, multilingual, multi faith, multi ethnic? In addition to this they also have a historical background in conflicts and war. The Kurdistan region is a newly developing region that has a diverse population and has had a historical past in continuous conflicts and war between the internal political parties. As well as this the presence of a political media system in the country has been a part of the conflicts in which has made the media language a huge reason for the distancing of the parties and the further deepening of the conflicts. That is why this research investigates the importance and role of the media language of its responsibility of creating coexists, the Kurdish channel in the Kurdistan region taken it as an example ,by using a survey method.